Pengaruh Variasi Kombinasi Konsentrasi Surfaktan Non Ionik (Span 60 Dan Peg-40 Hco) Terhadap Stabilitas Fisik Mikroemulsi Koenzym Q10 - Silvi Ayu Wulansari; Umarudin Umarudin (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Coenzyme Q10 is a compound that functions as an antioxidant with a large molecular weight of 863.36 g / mol and has lipophilic properties. This makes coenzyme Q10 need to be formulated to improve the solubility of the material and the delivery system in the skin. This study aims to determine the effect of various combinations of non-ionic surfactant concentrations (span 60 and PEG-40 HCO) on the physical stability of microemulsions. In this study Coenzyme, Q10 was formulated in oil-type microemulsion preparations in water. The oil used as the oil phase is rice bran oil with a combination of surfactant span 60 and PEG-40 HCO and 96% ethanol as a cosurfactant. the microemulsion was made in 4 microemulsion formulas namely FI, F2, F3, and F4, each formula was made 3 replications. Microemulsion preparations were evaluated after 24 hours after the preparations were made, observations made included organoleptic (shape, color, and phase formed), pH, viscosity, droplet size, zeta potential, and polydispersity index before and after centrifugation test with 10,000 rpm for 30 minutes. The research data were processed statistically using the Kruskal-Wallis analysis and Mann-Whitney follow-up tests. The results showed that the surfactant concentration affected physical characteristics (viscosity, droplet size, zeta potential, and polydispersity index) with a significantly different result (p <0.05) but the surfactant concentration did not affect the pH with the results not significantly different (p> 0, 05).